CHARACTERISTICS OF THE VALUE AND MEANINGFUL SPHERE OF YOUNG PEOPLE WHO PREFER CLUB LEISURE (Psychology Travelogs, 2023)
The article presents the results of a theoretical analysis and an empirical study of the problem of the value-meaning sphere of higher education students who spend their free time in clubs. Analysis of psychological literature on the problem of forming the value-meaning system of modern youth showed that Ukrainian youth are prone to anomic demoralization, authoritarianism, and social cynicism. As a result, young people do not develop a stable system of socially oriented values and meanings, which corresponds to the perspective of the development of a democratic society. The development of values and meanings in youth is largely influenced by the socio-cultural environment, in particular, the youth subculture, which includes preferences, slang, fashion, etc. Meanings of life, value orientations and specific life goals largely depend on the specifics of the subculture a young person enters. The study of prevailing life values and orientation to certain areas, which are characteristic of young people who lead club leisure, showed that the most important thing for them is the desire for a high level of material well-being, the conviction that material wealth is the main condition for life well-being. A high level of material well-being for such people is the basis for the development of a sense of self-importance and increased self-esteem. Physical attractiveness and health, raising the level of education, and broadening one's horizons are also important for them. Among the main life orientations that are meaningful at the moment, youth in this category are oriented towards the future and have specific goals. In addition, the process of achieving these goals is important for them. Although, they tend to mystify the events of their own biography, are prone to fatalism, and their goals and plans have no real basis in the present and are not supported by personal responsibility for their implementation.
Keywords: value-semantic sphere; subculture; club leisure; youth; students of higher education